Inhibition of choline kinase as an antiamoebic approach in entamoeba histolytica - Hui, Teh Zhi (2018)
Entamoeba histolytica is the causative parasite for amoebiasis which manifests into amoebic colitis or amoebic liver abscess. Patients with intestinal amoebiasis are traditionally treated with metronidazole. There is concern for metronidazole resistance and the resistance pathway has been discovered in E. histolytica. A new antiamoebic approach via CDP-choline pathway is explored in this study. Inhibition studies were carried out by inhibition of EhCK enzyme by some potential CK inhibitors and via EhCK gene knockdown using RNA interference. E. histolytica choline kinase (EhCK) showed preference for Mn2+ as cofactor instead of Mg2+ that is usually used by choline kinases from other species including human. The unique preference for Mn2+ suggests the possibility of EhCK specific inhibitors not affecting the human host CK (hCK). Km and Vmax of purified EhCK and hCKα2 proteins were determined by pyruvate kinase-lactate dehydrogenase (PK-LDH) coupled assay with Mn2+or Mg2+ as cofactors. The IC50 values for EhCK and hCKα2 were determined with several commercial CK inhibitors (CK37, HC-3, HDTAB, flavopiridol, and H-89). Selected inhibitors were incubated with E. histolytica trophozoites for 48 hours to determine the EC50 for each inhibitor. Silencing of gene encoding EhCK was carried out using duplex siRNA via soaking method and the gene expression level was measured by real-time qPCR. Transfection efficiency was assessed with fluorescence siGLO RISC-Free Control siRNA. Values of Km and Vmax of EhCK with Mn2+ as cofactor for choline substrate were 0.12 ± 0.030 mM and 34.12 ± 1.87 U/mg, respectively. For ATP substrate, the Km and Vmax were 1.61 ± 0.26 mM and 48.98 ± 2.14 U/mg, respectively. EhCK was much less efficient with Mg2+ cofactor. The Km values were higher (0.20 ± 0.044 mM for choline; 10.85 ± 2.33 mM for ATP) and the Vmax decreased (2.13 ± 0.14 U/mg for choline; 3.02 ± 0.37 U/mg for ATP). Km and Vmax hCKα2 in Mg2+ for choline substrate were 0.12 ± 0.012 mM and 71.4 ± 1.54 U/mg, respectively and for ATP substrate the values for Km and Vmax were 0.67 ± 0.085 mM and 113.6 ± 5.13 U/mg, respectively. Based on IC50 values for EhCK and hCKα2, three inhibitors, namely CK37 (60.64 ± 14.67 μM vs IC50 for hCKα2 68.41 ± 12.08 μM), flavopiridol (45.51 ± 15.50 μM vs IC50 for hCKα2 297.0 ± 80.50 μM), and H-89 (100.60 ± 17.41 μM vs IC50 for hCKα2 392.1 ± 36.62 μM) were more potent against EhCK than hCKα2. All inhibitors tested also exhibited lower potency with Mn2+ as the cofactor compared to Mg2+. Trophozoites growth inhibition showed that only HDTAB, H-89 and control drug metronidazole with EC50 values of 47.40 ± 7.22 μM, 32.44 ± 5.05 μM, and 1.73 ± 0.33 μM, respectively, could penetrate and induce cell death after 48-hour incubation. The highest transfection efficiency of 55% was obtained after soaking with 10 μg/mL of siGLO RISC-Free Control siRNA for 16 hours. siRNA concentration of 10 μg/mL was used for the transfection of positive control GAPDH, EhCK, and non-targeting GFP siRNAs. RNAi experiment concluded with positive control GAPDH downregulated by 99% while the level EhCK mRNA was downregulated by 47%. This study has identified potential EhCK inhibitors and siRNA for further modifications and testing to achieve higher potency against EhCK but not affecting hCK. The use of specific inhibitors and siRNA targeting EhCK could be novel approach to inhibit the growth of E. histolytica by interrupting the phospholipid synthesis pathway of this parasite.